Redefining EOR In Indonesia’s Oil & Gas Industry: A Novel Solution to Overcome Lengthy Lag Time from EOR Implementation In Indonesia Post Gross Split Fiscal System - Steven Chandra; Sudjati Rachmat (Indonesian Journal of Energy, 2018)
In the wake of a new fiscal system related to oil and gas industry in Indonesia, namely the gross split system, concerns have been risen due to the fact that the new regulation puts forward EOR as an obligation for oil and gas contractors in order to gain significant incentives to improve field economics. Although EOR itself is a mature and proven technologically and economically to alleviate oil production thus encouraging profitable business, it has to be realized that most greenfields in Indonesia are relatively small compared to previous discoveries or case studies encountered abroad, rendering EOR to be economically obsolete to be implemented in full field scale. This study presents a new concept and suggestions for stakeholders to implement massive tertiary recovery in oil reservoirs around Indonesia using the less expensive and more result oriented, reducing the need for lengthy procedure before full scale EOR can take place.